The scale insects: Its status, biology, ecology and management in tea plantations - Kakoti, Beauti; Deka, Bhabesh; Roy, Somnath; Babu, Azariah (Frontiers in Insect Science, 2023)
Scale insects are sap-sucking insects that reduce plant photosynthetic ability by sucking sap from leaves and causing significant damage to the tea crop in most tea-producing countries. The review includes a compilation of Coccoids on tea in major tea-growing countries as potential pests of tea. They suck the sap from tea leaves, which not only prevents further growth but also reduces the nutritional quality of the leaves by promoting the growth of sooty molds. However, due to the widespread use of organo-synthetic pesticides in recent decades, most insect pests have developed high levels of pesticide resistance, reducing the effectiveness of insecticide application. Bio-control agents are environmentally safe and produce long-term results while reducing the use of chemicals and other pesticides without disrupting the natural equilibrium. The scope of future studies and the plans for better management of this serious sucking pest of the tea plant are discussed in this review.